Emergency Response Demand and Supply: A GIS-Based Network Analysis for Fire Station’s Service Coverage Delineation in Kano Metropolis, Nigeria - Sulaiman Yunus; Julius Afolabi Falola; Ibrahim Musa Jaro (Geosfera Indonesia, 2023)
Inadequate fire emergency response infrastructure and a lack of defined service coverage remain key barriers to timely fire disaster response. This study is applied research which employed geospatial techniques and aimed at examining fire disaster emergency response demand and supply relationships with the view to delineating service coverage and locating more facilities for optimum coverage in Kano metropolis. Locations of the existing fire stations and fire incidents (2009-2019) were gathered through GPS surveying. Network data set were generated. Nearest Neighbor and Network Analysis (origin-destination, service coverage and location-allocation) were conducted to determine emergency response demand and supply relationships, service coverage area delineation and identifying best site for allocating new facilities within the metropolis respectively. It was found that no clearly defined service coverage exist as emergency response supply takes more than 4-8 times the NFPA travel standard, and with a great deal of overlapping response patterns. New service coverage areas were proposed and best sites for 8 firefighting facilities identified for optimum coverage. It is concluded that emergency fire disaster response demand and supply relationships within Kano metropolis is imbalanced, with extensive recurrent demand especially within the core area served by overstretched and inefficient response supply. This, therefore, implies continuous exposure of lives and properties to the menace of fire disaster in Kano metropolis.